2021
DOI: 10.1039/d1bm00659b
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen- and bubble-generating polymersomes for tumor-targeted and enhanced photothermal–photodynamic combination therapy

Abstract: As a common feature of the tumor microenvironment (TME), hypoxia significantly impede the effects of photodynamic therapy. Moreover, for tumor combination therapy, smart responsive and well-designed nanocarriers are highlighted to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…The encapsulation of PSs into specifically designed nanosized polymersomes with stimulus-triggered release of PSs has been reported in recent years, including temperature, pH, and light-induced release of the PSs [296,372,373]. For instance, Lanzilotto et al recently reported a system used for aPDT consisting of polymersomes of the tri-blockcopolymer poly(2-methyl-2-oxazoline)-block-poly-(dimethylsiloxane)-block-poly(2-methyl-2-oxazoline) (PMOXA34-PDMS6-PMOXA34) encapsulating water-soluble porphyrin derivatives [372].…”
Section: Polymersomesmentioning
confidence: 99%
“…The encapsulation of PSs into specifically designed nanosized polymersomes with stimulus-triggered release of PSs has been reported in recent years, including temperature, pH, and light-induced release of the PSs [296,372,373]. For instance, Lanzilotto et al recently reported a system used for aPDT consisting of polymersomes of the tri-blockcopolymer poly(2-methyl-2-oxazoline)-block-poly-(dimethylsiloxane)-block-poly(2-methyl-2-oxazoline) (PMOXA34-PDMS6-PMOXA34) encapsulating water-soluble porphyrin derivatives [372].…”
Section: Polymersomesmentioning
confidence: 99%
“…PDT is highly dependent on the availability of oxygen (34,35). Therefore, oxygen distribution in cells and tissues should be fully considered in the design of the light source and the choice of photosensitizer.…”
Section: Discussionmentioning
confidence: 99%
“…Nanoplatforms that catalyze the endogenous H 2 O 2 for in situ O 2 production have thus been extensively studied and applied. Li et al (2021b) prepared oxygen- and bubble-generating polymersomes nanomaterials (FIMPs), which used MnO 2 and indocyanine green, the hydrophobic photosensitizer, as the shell and NH 4 HCO 3 solution as the core, based on the reduction-responsive copolymer (poly (ε-caprolactone)-ss-poly (ethylene glycol)-ss-poly (ε-caprolactone) and 1,2-distearoyl- sn -glycero-3-phosphoethanolamine-N-[folate (polyethylene glycol)-2000]), to combine PTT and PDT in tumor treatments ( Figure 6 ). In vitro and in vivo experiments have shown that FIMPs can facilitate a high accumulation of drugs at the tumor site through EPR and folic acid-mediated targeting effects.…”
Section: Application Of Redox Nanomaterials In Disease Therapymentioning
confidence: 99%
“… Schematic illustration for the formulation and enhanced photothermal–photodynamic combination therapeutic mechanism of oxygen- and bubble-generating polymersomes (FIMPs). Reproduced with permission from ( Li et al, 2021b ) Copyright (2021) Royal Society of Chemistry. …”
Section: Application Of Redox Nanomaterials In Disease Therapymentioning
confidence: 99%